(untitled) (Globalization and Business, 2023)
The contemporary ultimate goal for any national government is to insure science-based economic developmentto achieve higher standard of leaving for citizens. Technological achievements are significant factors for modern global economic development. The new industrial revolution is fundamentally different from the old ones. The current one – named as fourth industrial revolution-creates the new environment of digital world. Fourth Industrial Revolution is the key issue on contemporary development agenda in academic, political and economic circles. Against the constant development of the information technologies, more and more business processes, products, goods, and services are impacted by innovations. This process entails the continuous evolution of business models, which eventually are becoming more and more digitalized. However, the digital development remains still an on-going process even in condition of COVID pandemic ratherthan a reality of every national economy. National Governments have to redouble their efforts to create better and larger infrastructure for the digital economy to grow. The ability of expanding business through physical infrastructure cannot be considered for granted in the digital economy. Not only physical infrastructure is enough for further digitalization. The creation of an ecosystem that systematically allows top innovations to be advanced globally still remains a key policy goals. Consequently, the national economic policy aiming at rising the welfare of the country has to pay particular attention to resource, mainly labour and capital, efficiency by providing basic infrastructure for facilitation of digitalization and increasing their expenditure on R&D to enable businesses and individuals effectively use novelties for creating competitive advantages to take stronger position in global markets.